2016
DOI: 10.1177/2167702616649365
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Quality and Alcohol-Related Social Reinforcement During Couples Interaction

Abstract: Individuals who are unhappy in their intimate partnerships are at risk for developing alcohol problems. But little is known about the mechanisms underlying this link. One possibility is that couples with poor relationship quality gain more reinforcement from alcohol in certain contexts—a possibility that has never previously been empirically examined. In the current study, 304 individuals (152 couples) were assigned to receive alcohol (target BAC .08%) or a non-alcoholic beverage. They then engaged in a confli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
1
9
1
Order By: Relevance
“…Thus, the viewpoint that alcohol increases how sociable, warm, and at ease one appears was supported. This is in line with the findings that alcohol promotes more positive social behavior and more positive and less negative affect (Fairbairn & Testa, 2017; Kirchner et al, 2006; Sayette et al, 2012; Winograd et al, 2017; Winograd et al, 2014) and is consistent with common lay alcohol outcome expectancies (e.g., Brown, Christiansen, & Goldman, 1987; Fromme, Stroot, & Kaplan, 1993). These results are also consistent with findings that people commonly choose to consume alcohol as a means of facilitating social motives (e.g., Kuntsche, Knibbe, Gmel, & Engels, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, the viewpoint that alcohol increases how sociable, warm, and at ease one appears was supported. This is in line with the findings that alcohol promotes more positive social behavior and more positive and less negative affect (Fairbairn & Testa, 2017; Kirchner et al, 2006; Sayette et al, 2012; Winograd et al, 2017; Winograd et al, 2014) and is consistent with common lay alcohol outcome expectancies (e.g., Brown, Christiansen, & Goldman, 1987; Fromme, Stroot, & Kaplan, 1993). These results are also consistent with findings that people commonly choose to consume alcohol as a means of facilitating social motives (e.g., Kuntsche, Knibbe, Gmel, & Engels, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…Another hypothesis is that given that parental AUD is a risk factor for lower dyadic functioning (Harter, 2000), couples in which one or both partners grow up with an affected parent may be at particular risk of using alcohol as a tool to improve their marital interactions (Fairbairn & Testa, 2016). More broadly, spouses who grew up with an AUD-affected parent may have other psychosocial liabilities that limit their ability to engage in the types of health-promoting behaviors typically associated with marriage.…”
Section: Discussionmentioning
confidence: 99%
“…Looking within the experimental realm, where researchers have examined effects of acute intoxication on relationship factors, a handful of studies have found detrimental effects of substance administration on the quality of social interaction between close relationship partners (Leonard & Roberts, 1998b; Samp & Monahan, 2009). However, the majority of studies have revealed no such detrimental effects (e.g., see Fairbairn, 2017), and many have observed a social-cohesive effect of drugs of abuse during social interaction (del Porto & Masur, 1984; Fairbairn & Testa, 2016). As noted by Leonard and colleagues, “although it seems implausible that there should be no causal influence [of substance use on close relationship functioning], the nature and strength of that causal influence are not clear” (Leonard & Eiden, 2007, p. 294).…”
Section: Substance Use and Close Social Bondsmentioning
confidence: 99%